Development and utilization of a new chemically‐induced soybean library with a high mutation density1 . Issue 1 (January 2017) - Li, Zhongfeng; Jiang, Lingxue; Ma, Yansong; Wei, Zhongyan; Hong, Huilong; Liu, Zhangxiong; Lei, Jinhui; Liu, Ying; Guan, Rongxia; Guo, Yong; Jin, Longguo; Zhang, Lijuan; et al.
Abstract: Mutagenized populations have provided important materials for introducing variation and identifying gene function in plants. In this study, an ethyl methanesulfonate (EMS)‐induced soybean ( Glycine max ) population, consisting of 21, 600 independent M2 lines, was developed. Over 1, 000 M4 (5) families, with diverse abnormal phenotypes for seed composition, seed shape, plant morphology and maturity that are stably expressed across different environments and generations were identified. Phenotypic analysis of the population led to the identification of a yellow pigmentation mutant, g yl, that displayed significantly decreased chlorophyll (Chl) content and abnormal chloroplast development. Sequence analysis showed that gyl is allelic to MinnGold, where a different single nucleotide polymorphism variation in the Mg‐chelatase subunit gene ( ChlI1a ) results in golden yellow leaves. A cleaved amplified polymorphic sequence marker was developed and may be applied to marker‐assisted selection for the golden yellow phenotype in soybean breeding. We show that the newly developed soybean EMS mutant population has potential for functional genomics research and genetic improvement in soybean. Abstract : A new ethyl methanesulfonate (EMS) ‐induced soybean ( Glycine max ) population was developed. Over one thousand mutants with diverse abnormal phenotypes across generations and environments were identified and stored in the National GenBank. Our study shows that the mutants have big potential for accelerating functional genomic research and genetic improvement in soybean.